If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 = 3(w + 7) + -5w Reorder the terms: 17 = 3(7 + w) + -5w 17 = (7 * 3 + w * 3) + -5w 17 = (21 + 3w) + -5w Combine like terms: 3w + -5w = -2w 17 = 21 + -2w Solving 17 = 21 + -2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '2w' to each side of the equation. 17 + 2w = 21 + -2w + 2w Combine like terms: -2w + 2w = 0 17 + 2w = 21 + 0 17 + 2w = 21 Add '-17' to each side of the equation. 17 + -17 + 2w = 21 + -17 Combine like terms: 17 + -17 = 0 0 + 2w = 21 + -17 2w = 21 + -17 Combine like terms: 21 + -17 = 4 2w = 4 Divide each side by '2'. w = 2 Simplifying w = 2
| 6n+15=42 | | 4x^2+6Y+2=0 | | 1n+7=35 | | 7.96*-100= | | 4x^2+24x-84=0 | | 5(n-2)=17 | | 2(2x-2)-(3x+1)=3(5-x) | | 3n*12=20 | | -6(4+2x)-7x=x-24 | | -8a+3=9+10a | | Log(9x)-log(2x-5)=log(6) | | -4+2x=-8 | | (4-5i)(4+5i)=0 | | 3m+21=4(m+4) | | 5(x-5)=25 | | 7x-(3x+1)=19 | | 8x+4(4c-3)=4(6+4)-4 | | -2xcubed+16xsquared+18x=0 | | 100x^2-400=0 | | 4.5y=2.5y+14 | | 6(x-3)-2(x-2)=10 | | 8n+24=2d+22 | | 1-2*(3x-1)/5=(x+8)/6-(4x-2)/3 | | 2m^2+20m+48=0 | | x-4+4x=6x+9-8 | | -3(x^2-2)-2(2x^2-1)= | | 222=95-w | | 22=95-w | | 16-2b=12 | | x^2+(2i-7)x+13-i=0 | | 4v+2=5v-8 | | (5x+3)(x)(2x-1)=210 |